eIF3k Domain-Containing Protein Regulates Conidiogenesis, Appressorium Turgor, Virulence, Stress Tolerance, and Physiological and Pathogenic Development of Magnaporthe oryzae Oryzae - Lin, Lili; Cao, Jiaying; Du, Anqiang; An, Qiuli; Chen, Xiaomin; Yuan, Shuangshuang; Batool, Wajjiha; Shabbir, Ammarah; Zhang, Dongmei; Wang, Zonghua; Norvienyeku, Justice (Frontiers in Plant Science, 2021)
The eukaryotic translation initiation factor 3 complex (eIF3) consists of essential and non-essential sub-complexes. The non-essential eIF3 complex subunits, including eIF3e, eIF3j, eIF3k, and eIF3l, modulate stress tolerance and enhance the lifespan of Neurospora crassa and Caenorhabditis elegans. However, there is limited knowledge on the role of the non-essential eIF3 sub-complex in the pathophysiological development of plant fungal pathogens. Here, we deployed genetic and biochemical techniques to explore the influence of a hypothetical protein containing eIF3k domain in Magnaporthe oryzae Oryzae (MoOeIF3k) on reproduction, hyphae morphogenesis, stress tolerance, and pathogenesis. Also, targeted disruption MoOeIF3k suppressed vegetative growth and asexual sporulation in the ∆MoOeif3k strains significantly. We demonstrated that MoOeIF3k promotes the initiation and the development of the rice blast disease by positively regulating the mobilization and degradation of glycogen, appressorium integrity, host penetration, and colonization during host-pathogen interaction. For the first time, we demonstrated that the eIF3k subunit supports the survival of the blast fungus by suppressing vegetative growth by possibly regulating the conversions and the utilization of stored cellular energy reserves under starvation. We also observed that the deletion MoOeIF3k accelerated the generation of rRNA generation in the ∆MoOeif3k strains with a corresponding increase in total protein output. In summary, this study unravels the pathophysiological significance of eIF3k filamentous fungi. These findings also underscored the need to systematically evaluate the individual subunits of the non-essential eIF3 sub-complex during host-pathogen interaction. Further studies are required to unravel the influence of synergetic coordination between translation and transcriptional regulatory machinery on the pathogenesis of filamentous fungi pathogens.